2020
DOI: 10.3738/21751463.3734
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect the Thermal Stability of Bovine Milk and the Use of Alcohol Test in the Milk Industry – A Review

Abstract: The dairy industry requires good quality milk with an adequate yield that does not affect the industrial process. Therefore, to produce safe food for consumers aiming to increase the shelf life of the product, the before mentioned industry makes use of heat treatment (pasteurization or UHT – Ultra-high Temperature processing). Milk must have adequate quality and high-temperature resistance; otherwise, thermal stability problems may occur. The alcohol or alizarin test is used in dairy farms to identify milk sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the past, the ethanol stability of milk was used as an indicator of its freshness and to provide information on the stability of raw milk at ultra-high temperatures and powder processing [ 11 , 12 ]. Thus, alcohol testing was extremely useful to the global dairy industry since it allowed acidic milk, such as colostrum or mastic milk, to be processed without causing quality issues or coagulation in the dairy pasteurizer’s heating plates [ 13 ]. Much attention has been devoted to the heat stability of camel milk in recent years [ 14 ], but there is relatively little published information on the effects of ethanol on camel milk protein stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the ethanol stability of milk was used as an indicator of its freshness and to provide information on the stability of raw milk at ultra-high temperatures and powder processing [ 11 , 12 ]. Thus, alcohol testing was extremely useful to the global dairy industry since it allowed acidic milk, such as colostrum or mastic milk, to be processed without causing quality issues or coagulation in the dairy pasteurizer’s heating plates [ 13 ]. Much attention has been devoted to the heat stability of camel milk in recent years [ 14 ], but there is relatively little published information on the effects of ethanol on camel milk protein stability.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is relevant to know how milk proteins are destabilized by ethanol from a technological point of view. Furthermore, Horne [ 12 ] and Rosa et al [ 13 ] reported that ethanol stability differs from one species to another. In comparison to cow milk, there is a scarcity of current understanding in the alcohol stability of camel milk.…”
Section: Introductionmentioning
confidence: 99%